2011
DOI: 10.1007/s11064-011-0489-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Amphetamine Exposure Effects on Dopaminergic Receptors and Transporter in Postnatal Rats

Abstract: We investigated the influence of prenatal amphetamine exposure (PAE) on dopamine (DA) receptors, and dopamine transporter (DAT) in various striatal and limbic subregions and locomotor activity induced by novel environmental conditions and amphetamine at two postnatal ages, 35 days old (prepubertal) and 60 days old (postpubertal). Experiments were carried out on pregnant female Sprague-Dawley rats, which were daily injected with either d-amphetamine sulfate (1 mg/kg) or saline solution (0.9%) for 11 days, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In contrast, at a postpubertal age, the authors instead measured an increase in the levels of DAT in the NAc and striatum, and a decrease in D2 receptor expression in the NAc shell. In addition, acute AMPH induces a marked decrease in locomotor activity in rats following prenatal AMPH exposure (Flores et al, 2011). These developmental and behavioral changes in animal models associated with in utero AMPH exposure provide insights to the mechanisms causing changes in affective, behavioral, and cognitive outcomes in exposed children.…”
Section: Amphetaminementioning
confidence: 98%
“…In contrast, at a postpubertal age, the authors instead measured an increase in the levels of DAT in the NAc and striatum, and a decrease in D2 receptor expression in the NAc shell. In addition, acute AMPH induces a marked decrease in locomotor activity in rats following prenatal AMPH exposure (Flores et al, 2011). These developmental and behavioral changes in animal models associated with in utero AMPH exposure provide insights to the mechanisms causing changes in affective, behavioral, and cognitive outcomes in exposed children.…”
Section: Amphetaminementioning
confidence: 98%
“…In an autoradiography study, Flores et al . demonstrated that SD rats had higher DAT density at 60 days postnatally than at 35 days postnatally 5 . Gordon et al .…”
Section: Discussionmentioning
confidence: 94%
“…Even in neuroscience studies, the effects of developmental changes in the brain are often neglected in study designs [3]. According to McCutcheon et al, 42 % of studies that describe the use of adult animals actually involve immature experimental animals [3]; moreover, previous studies that have evaluated postnatal dopamine transporter (DAT) density changes in rats have reported increased DAT density until rats reach the young adult stage [4,5]. Although comparable ages between humans and rodents show some differences among studies, 2- to 3-year-old humans are approximately equivalent in age to rats at postnatal day (pnd) 20-21; 4- to 11-year-old humans are approximately equivalent in age to rats at pnd 25-35; 12- to 18-year-old humans are approximately equivalent in age to rats at pnd 35-49; and humans > 20 years of age are approximately equivalent in age to rats at pnd > 60 [6].…”
Section: Introductionmentioning
confidence: 99%
“…These three studies found little if any evidence of behavioral teratogenicity. A more recent study in rats was conducted using only one dose level (1 mg/kg) of dextroamphetamine administered s.c. on GDs 11-21 and evaluated locomotor activity in individual cages on PNDs 35 and 60 (Flores, de Jesus Gomez-Villalobos, & Rodriguez-Sosa, 2011). A decrease in locomotor activity compared to controls was observed.…”
Section: Behavioral Effects Of Gestational Exposures To Amphetaminementioning
confidence: 99%